Examining the Effect of Lactation Yoga on Anxiety in Breastfeeding Mothers - Aspia Lamana; Titin Nuraini; Elsa Noftalina; Febti Kuswanti; Khuzaifah (Poltekkes Kemenkes Palu, 2026)
Background: Anxiety in breastfeeding mothers can inhibit the let-down reflex due to increased adrenaline and cortisol, leading to vasoconstriction in alveolar blood vessels. Non-pharmacological interventions, such as lactation yoga, may help alleviate this condition. Lactatio yoga is a gentle exercise that breastfeeding mothers can perform to relax the body while breastfeeding. Our objective is to assess the impact of lactation yoga on anxiety levels among breastfeeding mothers in the Kebong Public Health Center, Sintang Regency. Method: This study employed a pre-experimental one-group pretest–posttest design. Lactation yoga intervention was provided only to breastfeeding mothers aged 6 weeks to 6 months; the sample comprised 21 participants, selected through total sampling. Data were analyzed using the Wilcoxon test. Result: Post-intervention anxiety scores were significantly lower than pre-intervention scores (p= 0.001, p <0.005). Conclusion: Lactation yoga significantly reduces anxiety in breastfeeding mothers. Recommendation: Incorporating lactation yoga into maternal health programs may help decrease anxiety and promote the success of exclusive breastfeeding.